CUMULATIVE ANTIBIOGRAM IN THE SELECTION OF EMPIRIC ANTIBIOTIC THERAPY - Bachynska, O.V.; Doan, S.I.; Zakordonets, L.V.; V, V.; Макаренко, М.О.; Герасименко, О.А.; Gerasymenko, O.A.; Pavlenko, O.V. (World of Medicine and Biology, 2024)
Local microbiological monitoring was carried out based on the results of bacteriological studies of clinical samples from 892 patients in the departments of anesthesiology, intensive care and surgical departments in a multidisciplinary hospital. 1086 microorganisms were isolated, of which 837 isolates of bacterial pathogens (77.07 %) and 249 isolates of Candida fungi were isolated. Among the detected bacterial pathogens, gram-negative bacteria probably prevailed (p